2021
DOI: 10.3892/ol.2021.12950
|View full text |Cite
|
Sign up to set email alerts
|

Novel bone microenvironment model of castration‑resistant prostate cancer with chitosan fiber matrix and osteoblasts

Abstract: The interaction between prostate cancer cells and osteoblasts is essential for the development of bone metastasis. Previously, novel androgen receptor axis-targeted agents (ARATs) were approved for metastatic castration-naïve and non-metastatic castration-resistant prostate cancer (CRPC); both of which are pivotal for investigating the association between the bone microenvironment and tumors. The present study established a novel in vitro 3D microenvironment model that simulated the bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The observation and analysis of the spheroid area were performed and quantified using Cell 3 iMager duos (SCREEN Holdings Co., Ltd.) and ImageJ software, respectively. 29 The fold increase of the spheroid area was determined by the ratio between the spheroid area of each day and the spheroid area at day 0.…”
Section: Methodsmentioning
confidence: 99%
“…The observation and analysis of the spheroid area were performed and quantified using Cell 3 iMager duos (SCREEN Holdings Co., Ltd.) and ImageJ software, respectively. 29 The fold increase of the spheroid area was determined by the ratio between the spheroid area of each day and the spheroid area at day 0.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been suggested that adding dutasteride to endocrine therapy might have a more potent inhibitory effect on AR signaling in prostate cancer. Indeed, we and others have reported that a combination of abiraterone and dutasteride decreased intratumoral testosterone and DHT concentrations and showed excellent synergistic anticancer effects in CRPC C4‐2 cells 15,16 . In addition, Li et al reported that abiraterone was metabolized into Δ4‐abiraterone (D4A) by 3β‐hydroxysteroid dehydrogenase, and then further metabolized by 5α‐reductase into 3‐keto‐5α‐abiraterone, which is agonistic to AR and promotes prostate cancer progression 16,17 .…”
mentioning
confidence: 93%
“…Indeed, we and others have reported that a combination of abiraterone and dutasteride decreased intratumoral testosterone and DHT concentrations and showed excellent synergistic anticancer effects in CRPC C4-2 cells. 15,16 In addition, Li et al reported that abiraterone was metabolized into 4-abiraterone (D4A) by 3β-hydroxysteroid dehydrogenase, and then further metabolized by 5α-reductase into 3-keto-5αabiraterone, which is agonistic to AR and promotes prostate cancer progression. 16,17 Then, it is hypothesized that D4A concentration is increased by blocking 5α-reductase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond question, communication between bone and PCa cells is crucial in promoting the development of bone metastases . So far, few studies investigated this key aspect in 3D settings. …”
Section: Introductionmentioning
confidence: 99%